Avances en el desarrollo del cultivo de la mojarra (Cheirodon interruptus) como alternativa a la explotación de poblaciones silvestres - Maiztegui, Tomás (2009)
The use of Cheirodon interruptus as a sport fishing bait puts under serious pressure the pampean shallow lakes ecosystems, because it is mostly obtained from natural environments. This project aims to evaluate the possibility of developing the technological and biological know-how for a production system in captivity for sustainable use of the resource. We used a system with a low daily water renovation rate and a 150 % daily recirculation rate through a biofilter. Fishes in every ontogenetic stage in the system showed good health conditions and high acceptance to artificial diet formulations. Two spawning events were registered during spring season and the development of larvae through its juvenile stage went by with no further requirements than isolation from adults and granulometry variation of food. Although the character of this trial is just preliminar, we may conclude that a massive production system is possible, in order to make this bait market a sustainable activity not only in the commercial aspect but in its ecological as well.